Process for deep concentration of iron ores - Alexander Kurkov; Andrey Egorov; Sarra Scherbakova (International Mineral Processing Congress, 2014)
"Deep concentration of iron ores involves extraction, in addition to magnetite concentrate, of hematite and martite concentrates and recovery of other valuable components. A flotation technology was designed specifically for finely disseminated hematite ore, allowing producing saleable hematite concentrate containing 64-66% Fe. The main process challenge is caused by the presence of other ferruginous minerals such as carbonates, silicates, and phosphates, and fine hematite and martite mostly concentrated in the -0.044 mm fraction. Main operations of the processing circuit are removal of slime, flotation to remove impurities (carbonates, phosphates etc.) with an anionic phosphorous collector in an alkaline environment, hematite and martite flotation using same collector in a slightly acidic environment to produce commercial iron concentrate. Tailings of wet magnetic separation of magnetite containing 24.5% Fe and finely disseminated hematite ore containing 51% Fe were processed to produce iron concentrates with a yield of 15% and 50%, respectively, containing approximately 65% Fe and 5% of silica. Hematite flotation tailings had the highest content of gold (up to 0.09 - 0.11 g/t), while in other products it never exceeded 0.02 g/t. Using a Knelson concentrator was able to recover 40 to 45% of the gold into 3.31 g/t Au gravity concentrate. The success of gravity concentration is due to high gravitational contrast of gold to mostly quartz and aluminosilicates in the hematite flotation tailings. In general, the proposed process can be used as a solution to the challenge of selective concentration of finely disseminated iron minerals."